2020
DOI: 10.1097/acm.0000000000003689
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Inclusive Learning Environments and Professional Development in Medical Education Through an Identity and Inclusion Initiative

Abstract: In 2015, the Pritzker School of Medicine experienced increasing student interest in the changing sociopolitical landscape of the United States and the interaction of these events with student and patient identity. To address this interest, an Identity and Inclusion Steering Committee was formed and formally charged with “providing ongoing direction for programs and/or curricula at Pritzker that support an inclusive learning environment and promote respectful and effective communication with diverse patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…First, the time allotted for instruction on Asian health in the required quarter-long course on health disparities 19 for first-year medical students has tripled from 1 to 3 h. APAMSA and SAMSA students now speak at weekly interview day breakfasts with applicants about their experiences at Pritzker. Furthermore, the Identity and Inclusion (i2i) Steering Committee, 20 a student-and faculty-led group that develops programming pertinent to minority groups, hosted us at a general meeting to share our findings from the conference. The medical school also hosted programming for AAMSs and internal medicine residents to discuss negative experiences, such as microaggressions from More knowledge on Asian American health disparities and culturally competent care ''[I want] to educate myself on Asian American health disparities to better serve future Asian American patients.''…”
Section: Introductionmentioning
confidence: 99%
“…First, the time allotted for instruction on Asian health in the required quarter-long course on health disparities 19 for first-year medical students has tripled from 1 to 3 h. APAMSA and SAMSA students now speak at weekly interview day breakfasts with applicants about their experiences at Pritzker. Furthermore, the Identity and Inclusion (i2i) Steering Committee, 20 a student-and faculty-led group that develops programming pertinent to minority groups, hosted us at a general meeting to share our findings from the conference. The medical school also hosted programming for AAMSs and internal medicine residents to discuss negative experiences, such as microaggressions from More knowledge on Asian American health disparities and culturally competent care ''[I want] to educate myself on Asian American health disparities to better serve future Asian American patients.''…”
Section: Introductionmentioning
confidence: 99%
“…It is only by critically reflecting on weaknesses in the ways that theory underpins PIF interventions that we can bring those insights back to educational practice to ensure a robust approach to PIF among learners and professionals alike. Furthermore, only one of the interventions 65 in our review discussed intersectionality, a theoretical perspective that seeks to understand interactions between gender, race, and other identities, and the implications of power hierarchies that undergird them. 97,98 In a recent examination of PIF through the lens of minoritized physicians, Wyatt et al 99 concluded that race and ethnicity have been largely absent, invisible, or considered irrelevant within PIF research.…”
Section: S103mentioning
confidence: 99%
“…Such inclusion requires education leadership to apply a trauma-informed approach to building platforms for meaningful discourse around the most difficult challenges facing the training community and health care environment. 25…”
Section: Building Trustmentioning
confidence: 99%